2008
DOI: 10.1016/j.jasms.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of metal-mediated DNA binding of benzoxazole ligands by electrospray ionization mass spectrometry

Abstract: The binding of a series of benzoxazole analogs with different amide-and ester-linked side chains to duplex DNA in the absence and presence of divalent metal cations is examined. All ligands were found to form complexes with Ni 2ϩ , Cu 2ϩ , and Zn 2ϩ , with 2:1 ligand/metal cation binding stoichiometries dominating for ligands containing shorter side chains (2, 6, 7, and 8), while 1:1 complexes were the most abundant for ligands with long side chains (9, 10, and 11). Ligand binding with duplex DNA in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Despite the pronounced effect of 4-position substituents on Mg 2+ ion binding affinity in the 2-(2'-hydroxyphenyl)benzoxazole series, there are only relatively subtle variations in cytotoxicity. Our recent ESI-MS investigation of the metal ion binding of these compounds failed to demonstrate formation of Mg 2+ complexes in aqueous buffers, although complexes were observed in methanol [23]. These and previous ESI-MS studies [10] failed to demonstrate formation of ligand-Mg 2+ -DNA complexes with UK-1 or these analogs, although ligand-Cu 2+ -DNA complexes were readily observed.…”
Section: The Role Of Metal Ion Coordinationmentioning
confidence: 67%
See 1 more Smart Citation
“…Despite the pronounced effect of 4-position substituents on Mg 2+ ion binding affinity in the 2-(2'-hydroxyphenyl)benzoxazole series, there are only relatively subtle variations in cytotoxicity. Our recent ESI-MS investigation of the metal ion binding of these compounds failed to demonstrate formation of Mg 2+ complexes in aqueous buffers, although complexes were observed in methanol [23]. These and previous ESI-MS studies [10] failed to demonstrate formation of ligand-Mg 2+ -DNA complexes with UK-1 or these analogs, although ligand-Cu 2+ -DNA complexes were readily observed.…”
Section: The Role Of Metal Ion Coordinationmentioning
confidence: 67%
“…The cytotoxic analogs 1, 12-14, and 17 all demonstrate enhanced DNA binding by ESI-MS in the presence of Cu 2+ or Ni 2+ ; whereas, the relatively non-cytotoxic analogs 15 and 16 do not [23]. Even the 7-substituted benzoxazole 3 forms ligand-metal ion-DNA complexes, although these complexes are formed in much lower abundance when compared to those formed in the presence of 1 [10].…”
Section: The Role Of Metal Ion Coordinationmentioning
confidence: 96%
“…ESI-MS has proven to be useful for exploring DNA/ligand complexation in this context (23)(24)(25). One of the original studies reported the use of ESI-MS to examine the metal-mediated binding of chromomycin A 3 and mithramycin, two antitumor agents (23).…”
Section: Figurementioning
confidence: 99%
“…The metal-mediated binding of a series of benzoxazole and benzimidazole ligands (Figure 3) has also been investigated. In these studies (24,25), solutions containing DNA, one ligand, and either one divalent metal or no metal were analyzed by ESI-MS. These ligands were developed as analogs of UK-1, a natural product isolated from Streptomyces that possesses strong anticancer activity presumed to arise from its metal-mediated catalytic inhibition of human topoisomerase II.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation